Facts and figures on materials science and nanotechnology progress and investment - Talebian, Sepehr (2021)
J.C. acknowledges the European Research Council Starting Grant (ERC-StG-2019-848325). B.S. acknowledges Portuguese funds through FCT - Fundação para a Ciência e a Tecnologia/Ministério da Ciência, Tecnologia e Ensino Superior in the framework of the project "Institute for Research and Innovation in Health Sciences" - UID/BIM/ 04293/2019. T.R. acknowledges FCT for funding (CEECIND/ 00684/2018). Funding Information: To scrutinize the facts behind global nanotechnology development and investments, we analyzed research indicators in the academic sector and ensuing companies—engaged in myriad activities such as publications, patents, products, applications, instruments, and technologies—from publicly available data (). Aggregating global data from the 2000–2020 period, we conclude that North America and Europe are the key drivers in academic research, with each one hosting 41% of all research institutes worldwide. Interestingly, the United States (US) is the leading contributor in North America (92% of all research), whereas in Europe, research efforts are widespread among its countries. For example, Germany is Europe’s largest contributor, but represents only 23% of all research in the region. Arguably, such differing global distribution and prominence of selected countries is supported by more sustainable funding policies, irrespective of fluctuations in recent years. For example, the US NNI investments over the last 20 years, together with current priority funding provided by several National Institutes of Health or European Commission programs, are designed to incentivize frontier science and entrepreneurial endeavors. The European Commission has explicitly included nanotechnology as a theme in its research funding programs over the past decade and supports many scientists and institutions through the European Research Council and Marie Curie Actions. Furthermore, the Horizon 2020 program has reinforced the European Union (EU) nanotechnology sector by promoting opportunities in emerging nanotechnologies across a vast array of different areas. As such, expectations for the Horizon 2020 successor program—Horizon Europe—have been, up to recently, even higher when it comes to the translation of nanotechnology-enabled products. However, the impacts of the recently announced 14.3% cut to the program budget—as related to the EU emergency response to the ongoing COVID-19 pandemic—are now expected to cast a shadow over public investment in R&D in Europe. Publisher Copyright: © XXXX American Chemical Society.